The Lexical Decision Test as a Tool for Spanish University Students Placement - Fairclough, Marta; Ramírez Vera, Carlos J. (Íkala, Revista de Lenguaje y Cultura, 2009)
The lexical decision test has shown to be a practical measure of overall language proficiency. For this study, the effectiveness of a lexical decision test was measured with two groups of Spanish/English bilingual university students at four levels. The test was designed using a Spanish frequency dictionary (Davies, 2006). Participants marked only those items that they knew on a list of 200 words that included real words and non-words. A cloze-test was used as a comparison measure. The results of this pilot study indicate a high correlation between the two measures, and they suggest that the lexical test is a valid, cost effective testing tool that is easy to administer and score. Received: 16-07-08/ Accepted: 04-12-08 How to reference this articlé: Fairclough, M. & Ramirez Vera, C. J. (2009). La prueba de decisión léxica como herramienta para ubicar al estudiante de español en los programas universitarios. Íkala. 14(1), pp.85-99.